The Effect of the Variation of the Addition of Concrete Waste as a Substitute for Aggregate on the Compressive Strength of Concrete - Aqli, Rasiful; Andardi, Faris Rizal; Wahyudiono, Sandi (Universitas Ibn Khaldun Bogor, 2026)
This study investigates the utilization of recycled concrete aggregate as a replacement for natural aggregate in concrete mixtures. Various mixture variations were created by replacing both coarse and fine aggregates with recycled concrete waste at percentages of 20%, 40%, 60%, and 80%. Additionally, 10% rice husk ash was added as a partial replacement for cement. Material and mix design tests were conducted to achieve a target concrete compressive strength of 30 MPa. Cylindrical test specimens were cured for 28 days and then tested for their compressive strength. The test results were analyzed to determine the effect of recycled concrete waste on the concrete's compressive strength. This research is expected to provide a basis for the effective and sustainable use of recycled concrete waste in the construction industry.